Analysis of Supporting and Inhibiting Factors in the Implementation of Financial SIMDA - Widowati Widowati; A. Sakir; Malta Malta (Yayasan Ilomata, 2021)
To support regional autonomy the central government issued Law (UU) no. 23 of 2014 which has given authority to the Regional Government to manage and regulate its own government, this includes regional financial management which ultimately must be accountable to the public through the presentation of financial which are an element of Regional Financial Information. To carry out this mandate, the Simeulue Regency Government since 2007 has used the SIMDA Finance application as an information system for its financial management so that it can manage finances in an accountable and transparent manner. hinder the performance of the Financial SIMDA, which In the course of its implementation, the Simeulue Regency Government has found obstacles that gradually fix these inhibiting factors and implement supporting factors that can improve the performance of the Financial SIMDA. This study aims to determine the factors that hinder and support the implementation of SIMDA Finance in Simeulue Regency. This research method uses qualitative, research subjects consist of SIMDA Finance users who have used the application for more than three years, data collection techniques using observations, interviews and documents, data validity techniques using data triangulation. data analysis technique using NVIVO. The results show that the five main factors that support the implementation of SIMDA Finance in Simeulue Regency are software, leader commitment, network, hardware, and attitude of the implementer. Meanwhile, the five main factors that hinder the implementation of SIMDA Finance are human resources, software, networks, hardware and the attitude of the implementers. The factors that are the same between supporters and obstacles to SIMDA Finance are caused by researchers looking at different sides of these factors in implementing SIMDA Finance.